2018
DOI: 10.1111/php.12942
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Vanadium and Nitrogen in Photocatalytic Activity of VN‐Codoped TiO2 Photocatalyst

Abstract: In the present manuscript, we explore the VN-codoped TiO system intended to understand the role played by each dopant in synergistic enhancement in performance of TiO photocatalyst. The photocatalytic decomposition of organic pollutants in aqueous solution under visible light was used as a probe reaction to evaluate the performance of VN-codoped TiO samples with different V and N concentrations. An optical measurement of VN-codoped TiO shows considerable improved visible light absorption with increase in V-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…This corresponds to the study carried out by Varma et al as they remarked that V doping on TiO 2 promotes the visible light absorption compared to the N-doping, effectively narrowing the band gap value up to 2.42 eV. 223 However, it was also highlighted that a substantial increase in the V concentration could result in the formation of the recombination centers by creating oxygen vacancies to form a deep level within the band gap, reducing the photocatalytic activity of the TiO 2 . On the other hand, incorporating 2% loading of V on ZnS is shown to offer an astounding hydrogen generation that is 17-fold higher than pure ZnS.…”
Section: V-based Ldhsupporting
confidence: 85%
“…This corresponds to the study carried out by Varma et al as they remarked that V doping on TiO 2 promotes the visible light absorption compared to the N-doping, effectively narrowing the band gap value up to 2.42 eV. 223 However, it was also highlighted that a substantial increase in the V concentration could result in the formation of the recombination centers by creating oxygen vacancies to form a deep level within the band gap, reducing the photocatalytic activity of the TiO 2 . On the other hand, incorporating 2% loading of V on ZnS is shown to offer an astounding hydrogen generation that is 17-fold higher than pure ZnS.…”
Section: V-based Ldhsupporting
confidence: 85%
“…After being doped with nitrogen, the degradation efficiency reached to 92%, revealing that the photocatalytic performance was distinctly enhanced. Previous research studies have manifested that photocatalytic activity depends on many properties of the catalyst, including the bandgap energy, the surface structure, separation of photoinduced electron-hole pairs, extent of crystallinity, the surface adsorbed hydroxyl/ water species and nature of pollutant [29,67,68]. In the present work, the observed higher photocatalytic performance of the N-KTTO sample could be attributed to the several beneficial effects produced by the doping of N into the lattice of KTTO.…”
Section: Photocatalytic Activity Studiesmentioning
confidence: 49%
“…Chakinala et al also reported enhancement in dye degradation by using bimetallic bismuth–silver-doped TiO 2 (Bi–Ag/TiO 2 ). Bi–Ag/TiO 2 showed 100% photodegradation of dye molecules attributed to the synergistic action of Bi and Ag on TiO 2 by charge separation, increased e-transfer, and high ability to absorb in the visible light range …”
Section: Recent Research Carried Out In Wastewater Treatment Through ...mentioning
confidence: 99%